Rumen degradation and transit kinetics of particle size fractions from three different roughages - San Vicente U.; De Vega A.; Guada J.A.; Castrillo C. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Although both degradation and transit kinetics parameters are needed to estimate the effective degradability, no attempts appear to have been made in order to determine them on the same particle size populations. This is important as degradation kinetics of the whole diet should be a composite of individual rates of the different particles sizes making up that diet multiplied by their relative contribution. However, some interactions between microbial populations attaching to different particles may occur making this not being so. A similar concern arises when studying transit kinetics. It has been clearly demonstrated that the kinetic behaviour of the whole digesta cannot be determined by its labelling with external markers, which should only be applied to particles in a relatively narrowly defined range of sizes when estimates of particle mean retention time are to be made. The objectives of the present study were: (1) to determine the effect of forage quality (untreated barley straw, ammonia-treated barley straw and lucerne hay) and particle size on their in situ degradation kinetics and rates of outflow, and (2) to determine if the behaviour of the whole forage may be estimated from their particle sizes. In a changeover design, chopped untreated straw, ammonia-treated straw and lucerne hay were offered ad libitum to three sheep fitted with rumen and duodenal cannulae. Milled (3-mm screen) subsamples of these forages and five particle size families (> 1.2, 1.2 to 0.6, 0.6 to 0.3, 0.3 to 0.15 and 0.15 to 0.045 mm) obtained by wet sieving of the ground material were incubated in the rumen for up to 96 h to study degradation kinetics. Intraruminal doses of Yb-labelled whole ground (3-mm screen) forages and particle size fractions were also given to estimate outflow rates. Extent and fractional rate of degradation of both dry matter and neutral detergent fibre varied between whole roughages and between particle size populations within each forage, with no specific pattern of variation between these latter. Rumen fractional outflow rate was also affected by roughage and particle size, the smaller the size the faster the rate. Although there were large differences between degradation kinetics, fractional outflow rate and effective degradability of whole ground samples and the weighed means estimated from the different particle size populations, these did not reach statistical significance. It was concluded that the nylon bag technique does not completely mimic the behaviour of the composite of the different particle sizes constituting the material incubated, which may lead to severe errors when estimating degradation and transit.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)